Exploration of critical literacy skills in teaching environmental issues to early childhood in the coastal region - Hardiyanti, Waode Eti; Arif, Rifda Mardian; Sulkifly, Sulkifly (Universitas Ahmad Dahlan, 2024)
With the amount of abundant information in an online environment, critical literacy is needed to encounter misinformation and disinformation. Critical literacy can be taught from the early age to strength the ability to understand information and to think the meaning of information, stories, events, pictures and others. The research aim was to explore the critical literacy activities in early childhood education using a picture book and contextual setting with the theme of environment activities. The research used a qualitative approach using thematic analysis. Themes were gathered through observations and conversations with children. All information and patterns were coded and interpreted to create themes. The sample used purposive sampling, from 13 children aged 5 to 6-year-old in the coastal region of the Tomini Gulf during their literacy activities. The results showed that children had an awareness to connect the issue from the topic to their daily lives. These activities give children the chance to voice their opinion and solution even though the exploration to this activity has not been fully maximized. Lastly, children engaged in the literacy activity through identifying and creating meaning from the pictures and other clues of the book. Therefore, implementing critical literacy should integrate familiar settings and picture books that in line to children’s literacy.